2004
DOI: 10.1172/jci22220
|View full text |Cite
|
Sign up to set email alerts
|

Atrogin-1/muscle atrophy F-box inhibits calcineurin-dependent cardiac hypertrophy by participating in an SCF ubiquitin ligase complex

Abstract: Calcineurin, which binds to the Z-disc in cardiomyocytes via α-actinin, promotes cardiac hypertrophy in response to numerous pathologic stimuli. However, the endogenous mechanisms regulating calcineurin activity in cardiac muscle are not well understood. We demonstrate that a muscle-specific F-box protein called atrogin-1, or muscle atrophy F-box, directly interacts with calcineurin A and α-actinin-2 at the Z-disc of cardiomyocytes. Atrogin-1 associates with Skp1, Cul1, and Roc1 to assemble an SCF atrogin-1 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
150
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(153 citation statements)
references
References 55 publications
3
150
0
Order By: Relevance
“…We have also demonstrated the treatment potential of Fbxo32 through Berberine, which is consistent with a study using a cardiomyocyte-specific Fbxo32-overexpression mouse model to show resistance against TAC-induced hypertrophy through PP2B downregulation. 11 However, we do not exclude the possibility that Berberine activates other antihypertrophic pathways as previous studies have indicated upregulation of autophagy. 10,41 Together, this study highlights the novel components, Smad3 and Fbxo32, as well as Pak1 itself as attractive drug targets for future studies on therapeutic treatment in halting or reversing the progression of hypertrophy.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We have also demonstrated the treatment potential of Fbxo32 through Berberine, which is consistent with a study using a cardiomyocyte-specific Fbxo32-overexpression mouse model to show resistance against TAC-induced hypertrophy through PP2B downregulation. 11 However, we do not exclude the possibility that Berberine activates other antihypertrophic pathways as previous studies have indicated upregulation of autophagy. 10,41 Together, this study highlights the novel components, Smad3 and Fbxo32, as well as Pak1 itself as attractive drug targets for future studies on therapeutic treatment in halting or reversing the progression of hypertrophy.…”
Section: Discussionmentioning
confidence: 71%
“…12,13 In cardiomyocytes, Fbxo32 was shown to colocalize with calcineurin (PP2B); furthermore, overexpression of Fbxo32 reduced PP2B levels resulting in cytoplasmic retention of the transcription factor, nuclear factor of activated T cells (NFAT), which in turn prevents its prohypertrophic effects. 11,[14][15][16] P21-activated kinase 1 (Pak1) has been discovered as an important serine/threonine kinase with crucial functions in the heart. [17][18][19] It belongs to the group I Pak family and is activated by GTP-bound Cdc42/Rac1 GTPases.…”
mentioning
confidence: 99%
“…Numerous studies have demonstrated that E3 ubiquitin ligases play important roles in protecting myocardial infarction, cardiac hypertrophy and fibrosis [15,16,18,24,25,27,28,29]. CHIP has been identified as an E3 ubiquitin ligase/chaperone protein that is highly expressed in the various tissues and cell types [26].…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was performed as described [24,25]. Fifty µg protein lysates were separated by 10% SDS-PAGE and then transferred to nitrocellulose membranes (Bio-Rad), the membranes were incubated with primary antibody against p53 (1:500), CHIP (1:500; Santa Cruz Biotechnology, Santa Cruz, CA) and β-actin (Cell Signaling Technology, Beverly, MA, 1:3000) at 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Neonatal rat cardiomyocytes were isolated by enzymatic disassociation of 1-day-old SD rats as described previously [20]. Recombinant adenoviruses expressing green fluorescent protein (Ad-GFP) or Nrdp1 (Ad-Nrdp1) driven by the cytomegalovirus promoter were generated by the use of the Ad-Easy system (MP Biomedicals Inc.) [20].…”
Section: Methodsmentioning
confidence: 99%